Isokinetic muscle strength and hiking performance in elite sailors - Aagaard, P.; Beyer, N.; Simonsen, E. B.; Larsson, B.; Magnusson, S. P.; Kjaer, M. (Scandinavian Journal of Medicine & Science in Sports, 1998)
The aim of the present study was to describe the isokinetic strength profile and its relation to hiking performance in male (SM, n = 15) and female (SF, n = 6) elite sailors compared to a group of male control subjects (CM, n = 8) similar in age, anthropometry and level of fitness. Eccentric knee extension strength was higher in SM compared to CM (P < 0.01). Furthermore, SM were stronger during trunk extension (P < 0.05), but not during trunk flexion compared to CM. Overall muscle strength was lower in SF compared to SM (P < 0.01) and CM (P < 0.05), except for eccentric knee extension strength, where SF and CM did not differ (P > 0.05). Hiking performance correlated to maximal eccentric and isometric knee extensor strength in SF (rs = 0.83-0.88, P < 0.05) and in CM (rs = 0.73-0.77, P < 0.05) and to maximal eccentric knee extensor strength at high velocity in SM (rs = 0.46-0.54, P < 0.05). For a subgroup of hikers in SM (n = 8), hiking performance correlated to maximal isometric-eccentric knee extensor strength (rs = 0.67-0.74, P < 0.05), whereas no correlations emerged for the non-hikers (n = 7). Few correlations were observed between hiking performance and maximal concentric trunk flexor strength (rs = 0.69-0.92, P < 0.05). Unexpectedly, in SM correlations also were observed between hiking performance and maximal strength of the trunk extensors (rs = 0.46-0.53, hiker subgroup: rs = 0.64-0.67, P < 0.05). In conclusion, notably high levels of maximal eccentric knee extensor strength were observed for the male and female elite sailors examined in the present study. Furthermore, the present results suggest that hiking performance depends in part on maximal isometric-eccentric knee extensor strength. The maximal strength of the trunk extensors, which potentially stabilizes the lower back and spine, also seems to have some importance for the hiking performance of top-level sailors.